2018
DOI: 10.1002/jbmr.3616
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drug Prescriptions Are Associated With Increased Stress Fracture Diagnosis in the US Army Population

Abstract: Stress fractures are common in military personnel and endurance athletes, and nonsteroidal anti‐inflammatory drug (NSAID) use is widespread in these populations. NSAIDs inhibit prostaglandin synthesis, which blunts the anabolic response of bone to physical activity and could therefore increase risk of stress fracture. The objective of this study was to determine whether prescribed NSAIDs were associated with stress fracture diagnoses among US Army soldiers. We also aimed to establish whether acetaminophen, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 49 publications
(97 reference statements)
3
18
0
2
Order By: Relevance
“…In a case-control study of the entire US Army population between 2002 and 2011, prescribed NSAIDs were associated with a nearly 3-fold increased risk of stress fracture. 21 In this study, soldiers prescribed NSAIDs during rigorous initial military training had a 5.3-fold greater risk for stress fracture compared to soldiers in initial military training who were not prescribed NSAIDs. 21 The increased risk of stress fracture with NSAID prescription during initial military training, a period of heightened physical activity, indicated a significant negative impact of NSAID use on stress fracture risk.…”
Section: Nsaids and Stress Fracture Riskmentioning
confidence: 70%
See 3 more Smart Citations
“…In a case-control study of the entire US Army population between 2002 and 2011, prescribed NSAIDs were associated with a nearly 3-fold increased risk of stress fracture. 21 In this study, soldiers prescribed NSAIDs during rigorous initial military training had a 5.3-fold greater risk for stress fracture compared to soldiers in initial military training who were not prescribed NSAIDs. 21 The increased risk of stress fracture with NSAID prescription during initial military training, a period of heightened physical activity, indicated a significant negative impact of NSAID use on stress fracture risk.…”
Section: Nsaids and Stress Fracture Riskmentioning
confidence: 70%
“…21 In this study, soldiers prescribed NSAIDs during rigorous initial military training had a 5.3-fold greater risk for stress fracture compared to soldiers in initial military training who were not prescribed NSAIDs. 21 The increased risk of stress fracture with NSAID prescription during initial military training, a period of heightened physical activity, indicated a significant negative impact of NSAID use on stress fracture risk. This has important implications for other populations who may increase physical training for athletic and fitness goals.…”
Section: Nsaids and Stress Fracture Riskmentioning
confidence: 70%
See 2 more Smart Citations
“…Thus, runners seem to obtain some benefit from NSAIDs, 28 but there is concern for SF and other bone injuries. A study by Hughes et al 29 found that NSAID prescription increased risk for SFs more than 3-fold in soldiers during periods of regular activity and more than 5-fold during periods of more heightened physical activity. These results are believed to be due to de- creased bone anabolism in response to loading after taking NSAIDS, possibly due to attenuation of prostaglandin production.…”
Section: Discussionmentioning
confidence: 99%